Competitiveness and the Housing Market in Ireland - Dermot P. Coates; Karen Hogan; Erika Valiukaite (National Competitiveness and Productivity Council (NCPC), 2024)
The NCPC believes the housing market is currently inhibiting Ireland's competitiveness performance and undermines potential improvements in sustainable growth and well-being. Addressing labour market constraints is crucial for Ireland's ability to meet targets under Housing for All, as well as retrofitting and emissions targets under the Climate Action Plan. The NCPC believes that close attention should be given to the competing demands for labour across the construction sector and, in particular, the impact that this has on younger people competing in the housing market. Further, the NCPC believes that greater adoption of Modern Methods of Construction is crucial to reduce pressures for labour demand in the construction sector.
Keywords: 330